Modeling of Three-dimensional Unsteady Wake Past a Large Migratory Bird during Flapping Flight - F., Beaumont; F., Bogard; S., Murer; Matim, Polidori G. (WSEAS TRANSACTIONS ON FLUID MECHANICS, 2022)
This preliminary study aimed to model the aerodynamic behavior of a large migratory bird during a forward flapping flight. Computational Fluid Dynamics (CFD) was used to model the flow around and in the wake of a Canada Goose flying at an altitude of 1000m and a speed of 13.9m/sec. Flapping of the wings was modeled through dynamic meshing and subroutines implemented in a computational code using the Finite Volumes method. Monitoring of the flow quantities during the unsteady calculation revealed a close relationship between the wing-flapping dynamics and the cyclic variation of the forces acting on the bird. Postprocessing of the 3D results revealed a complex flow pattern mainly composed of two contra-rotating vortices developing at the wingtip. In a perpendicular plane to the main flow direction, we demonstrated that the bird's wake can be divided into two distinct zones: the downwash zone and the upwash zone. The latter is used by birds flying in formation to reduce their energy expenditure. We have also shown that when the bird flaps its wings, the trail of upwash left by the wingtips moves up and down in a wave-like motion. Further studies, which will include several birds, will be necessary to understand all the aerodynamic implications related to the flight of migratory birds in formation.